Interrelationship among Liquidity, Regulatory Capital and Profitability- A Study on Indian Banks - Sudipa Roy; Arun Kumar Misra; Purna Chandra Padhan; Molla Ramizur Rahman (Cogent Economics & Finance, 2019)
Liquidity is the ability of a bank to fund assets and meet obligations, as they become due, at reasonable costs. Technological and financial innovations have impacted the management of liquidity in banks. Declining ability to rely on core deposits, increased reliance on capital markets and recent turmoil in financial markets have created new challenges for banks in managing liquidity. The current study has discussed theories, indicators, factors influencing bank liquidity, and its implications on bank's capital and profitability. It has empirically analyzed the determinants of liquidity through Arellano-Bond estimates and studied the interrelationship of liquidity, regulatory capital, and profitability through 2-SLS system equations. It has found that bank size, profitability, leverage, net interest margin, CRAR, gross non-performing loans, and Central Bank Policy Rate are the significant determinants of banks' liquidity. The interactive effects among liquidity, profitability, and regulatory capital convey that banks can be more liquid with less profit, but less risky with more liquidity.
Keywords: 330; Bank liquidity; regulatory capital; bank profitability; 2SLS; panel data